Financial management behavior: The role of financial knowledge, financial attitude, and personality - Adelia Dwi Nurisaputri; Muhammad Ali Fikri; Eka Shinta Windikasari; Made Galih Wisnu Wardana (Kompartemen: Jurnal Ilmiah Akuntansi)
Financial management is an important instrument to improve the well-being of individuals. Individuals must have an understanding of financial management to make financial decisions. This study aims to find out how financial knowledge, financial attitudes, and personality affect financial management behavior. The respondents of this study amounted to 95 from micro, small, and medium enterprises in the batik sector in Yogyakarta. SPSS software is used to process research data. The results show that personality, financial attitudes, and financial knowledge improve financial management behavior. The conclusion of this study explains how individual financial management behavior can be improved with financial knowledge, financial attitudes, and personality.